2021
DOI: 10.24215/23143924e022
|View full text |Cite
|
Sign up to set email alerts
|

Acceso a la literatura científica desde Sci-Hub

Abstract: La comercialización de la información científica y las barreras de pago para su acceso se han convertido en una de las problemáticas más debatidas en las últimas décadas. El movimiento internacional de acceso abierto ha propuesto vías para favorecer su acceso y, a su vez, distintos actores han impulsado otras estrategias como sitios piratas para la descarga. En este artículo estudiamos el uso que se hace de Sci-Hub en Argentina a partir de un análisis cuantitativo de las estadísticas de descargas disponibles h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…From the five options presented, it was observed that those who reported using these routes indicated both practical and value-related concerns, and it is worth noting the homogeneity among the different disciplinary areas (Figure 3). In response to the first option, the impossibility of accessing the information in any other way attracts 75% of support, which coincides with the research into downloads from Sci-Hub in Argentina (Monti and Unzurrunzaga 2021). It also highlights that 38% of those who answered the survey mentioned the relative ease of access compared to other legal services.…”
Section: Motivation For Using Illegal Routesmentioning
confidence: 74%
“…From the five options presented, it was observed that those who reported using these routes indicated both practical and value-related concerns, and it is worth noting the homogeneity among the different disciplinary areas (Figure 3). In response to the first option, the impossibility of accessing the information in any other way attracts 75% of support, which coincides with the research into downloads from Sci-Hub in Argentina (Monti and Unzurrunzaga 2021). It also highlights that 38% of those who answered the survey mentioned the relative ease of access compared to other legal services.…”
Section: Motivation For Using Illegal Routesmentioning
confidence: 74%